2022
DOI: 10.1088/2058-8585/ac9f54
|View full text |Cite
|
Sign up to set email alerts
|

Shellac-paper composite as a green substrate for printed electronics

Abstract: Printed electronic devices that sense and communicate data will become ubiquitous as the Internet of Things continues to grow. Devices that are low cost and disposable will revolutionize areas such as smart packaging, but a major challenge in this field is the reliance on plastic substrates such as polyethylene terephthalate. Plastics discarded in landfills degrade to form micro- and nanoplastics that are hazardous to humans, animals, and aquatic systems. Replacing plastics with paper substrates is a greener a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 80 publications
1
8
0
Order By: Relevance
“…Figures 3(b) and (c) show the slight decrease in the contact angle of the drop of deionized water, indicating the trend of increasing hydrophilicity with added shellac layers. This observation corresponds to work [19], where with the additional shellac layer contact angle decreased. It was also observed that the addition of shellac layers strongly influenced the roughness of the surface.…”
Section: Shellac-based Paper Qualitysupporting
confidence: 67%
See 2 more Smart Citations
“…Figures 3(b) and (c) show the slight decrease in the contact angle of the drop of deionized water, indicating the trend of increasing hydrophilicity with added shellac layers. This observation corresponds to work [19], where with the additional shellac layer contact angle decreased. It was also observed that the addition of shellac layers strongly influenced the roughness of the surface.…”
Section: Shellac-based Paper Qualitysupporting
confidence: 67%
“…A 200 mg ml −1 shellac solution was prepared by dissolving 800 g of Kusmi seedlac in 4 liters of anhydrous ethanol by agitating the mixture for 90 min at 150 rpm using an orbital shaker [19]. The mixture was subsequently allowed to rest for 24 h to permit the wax and other debris to settle.…”
Section: Materials Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Cellulose-based materials have been proposed so far in various works as green PCB substrates. Cellulose and nanocellulose substrates have many advantages, such as flexibility, biodegradability, recyclability, and low cost, but they suffer high roughness, moisture sensitivity, and poor barrier properties, all significant drawbacks in electronics, where smooth and humidity-insensitive substrates are required . Another approach to make green PCBs relies on including waste from the agricultural and farming sector such as lignin, rice husks, banana fibers, and chicken feather fibers, at high percentages reaching even more than 50% by weight, inside an epoxy resin. Nevertheless, epoxy resin is still present as binder in those substrates with all of the end-of-life issues previously described.…”
Section: Introductionmentioning
confidence: 99%
“…3 Prior research delved into the realm of 3D printing techniques for fabricating electrical traces. 4,5 These investigations have ventured into diverse materials 6 and patterns, 7 leveraging ink-jet printing to create intricate electrical pathways. Within this body of work, however, a conspicuous research gap exists: a comprehensive understanding of how ink deposition and variations in trace paths impact the frequency and amplitude of the 3Dprinted antennas remains elusive.…”
Section: Introductionmentioning
confidence: 99%